2019
DOI: 10.1186/s13041-019-0497-5
|View full text |Cite
|
Sign up to set email alerts
|

Anterior insular cortex mediates hyperalgesia induced by chronic pancreatitis in rats

Abstract: Central sensitization plays a pivotal role in the maintenance of chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. This study was designed to examine the role of anterior insular cortex (aIC) in the pathogenesis of hyperalgesia in a rat model of CP. CP was induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). Abdomen hyperalgesia and anxiety were assessed by von Frey filament and open field tests, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…Unfortunately, much less focus has been directed toward the relief of the affective dimension of pancreatitis-related pain in both clinical and preclinical studies. In this study, we found that CP rats exhibited hypolocomotion and decreased exploratory behavior both in the open field and elevated plus maze tests, consistent with prior behavioral observations in VH rats induced by irritable bowel syndrome and chronic pancreatitis [31,34].…”
Section: Tnbs-induced Anxiety In Cp Ratssupporting
confidence: 90%
See 1 more Smart Citation
“…Unfortunately, much less focus has been directed toward the relief of the affective dimension of pancreatitis-related pain in both clinical and preclinical studies. In this study, we found that CP rats exhibited hypolocomotion and decreased exploratory behavior both in the open field and elevated plus maze tests, consistent with prior behavioral observations in VH rats induced by irritable bowel syndrome and chronic pancreatitis [31,34].…”
Section: Tnbs-induced Anxiety In Cp Ratssupporting
confidence: 90%
“…Sham rats exhibited a transient decrease of AWT, which reached a minimum on POD 3 and returned to baseline on POD 14. This phenomenon was also seen in our previous study, and was owing to post-operative pain [34]. Compared to sham rats, CP rats had a lower AWT from POD 7 to 35 (Fig.…”
Section: Tnbs-induced Abdominal Hyperalgesia and Hypolocomotionsupporting
confidence: 86%
“…One of which, the anterior cingulate cortex (ACC) that receives sensitive information via the thalamus and projects to the insular cortex (IC) has been well-characterized [37,38]. ACC hyperexcitability is associated to higher levels of pain [39], and glia activation can trigger hyperexcitability modulating neuronal channel function [40]. Furthermore, inflammatory markers in ACC are linked to pain sensitization [4143], thus we aimed to test whether dopaminergic dysfunction underlying ADHD symptoms could cause ACC inflammation, so, consequently reducing inflammation would alleviate ADHD symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…The anterior insular cortex (aIC) is also highly implicated in feeding behavior and pain perception [18][19][20], and tracing studies in rodents have shown that the NAc receives glutamatergic input from the aIC [21].…”
Section: Introductionmentioning
confidence: 99%